The Volume and Intensity of Motor Activity in the Physical Education Classes - Goran V. Šekeljić; Milovan V. Stamatović (University of Belgrade, Teacher Education Faculty, 2018)
The realisation of the majority of objectives of physical education classes is based on the motor activity of students. Previous studies have shown that the activity of students during class is very low (Božović, 2011; Đokić, 2014; Marković et al., 2012; McKenzie, 2006; Simons-Morton, Petrović, 2010; Taylor et al., 1994). The goal of this research was to determine how the motor activity of students in Physical Education classes contributes to the fulfillment of the recommendations related to the physical activity of children. The study of Tudor-Loki and others (Tudor-Locke et al., 2011) indicates that in one day boys should make, on average, between thirteen and fifteen thousand steps, and girls between eleven and twelve thousand steps. In addition, we wanted to determine whether there were any differences in the number of steps made during lessons where different subject areas were covered (athletics, gymnastics, elementary games) and whether the feedback on a realised activity, available during and after practice, can serve as a basis for increasing students' active time during a lesson and facilitating the planning of the subsequent lessons. In this research, the volume of motor activity is expressed as the number of steps and the measurement was performed with a pedometer. The monitoring of one male student and one female student of the first grade of primary school was carried out during thirty-five classes of different subjects. In the Physical Education class, the respondents realised between 2013 and 4875 steps. They covered the distance ranging between 1309 and 2490 meters. The average intensity of activities during the class was over eighty steps per minute. The smallest number of steps (2254 boys and 2404 girls) and the shortest active time (50%) were realised in the gymnastics class. The biggest number of steps (4721 boys and 4430 girls) and the longest active time (80%) were realised in the athletics class. The primary school teachers involved in the research claim that the information obtained by using a pedometer helps them to plan their lessons and that the data on the number of covered steps can help them evaluate the quality of their lessons in terms of students' physiological load.